Non-rigid multi-frame registration of cell nuclei in live cell fluorescence microscopy image data - Tektonidis, Marco; Kim, Il-Han; Chen, Yi-Chun M.; Eils, Roland; Spector, David L.; Rohr, Karl (Medical image analysis, 2015)
The analysis of the motion of subcellular particles in live cell microscopy images is essential for understanding biological processes within cells. For accurate quantification of the particle motion, compensation of the motion and deformation of the cell nucleus is required. We introduce a non-rigid multi-frame registration approach for live cell fluorescence microscopy image data. Compared to existing approaches using pairwise registration, our approach exploits information from multiple consecutive images simultaneously to improve the registration accuracy. We present three intensity-based variants of the multi-frame registration approach and we investigate two different temporal weighting schemes. The approach has been successfully applied to synthetic and live cell microscopy image sequences, and an experimental comparison with non-rigid pairwise registration has been carried out.
Online 11 August 2014
Gesehen am 30.06.2020